Correlation of temperature with galvanic corrosion behaviour of copper alloys based on wire beam electrode. (4th July 2018) - Chen, Chuan; Xu, Yun-Xiang; Zhong, Qing-Dong; Li, Yu-Lin; Cheng, Y. Frank; Li, Qian
ABSTRACT: Galvanic corrosion behaviour of copper and copper alloys in chloride solution (0.6 M NaCl) under different temperature conditions (35°C, 55°C and 80°C) was investigated by the wire beam electrode (WBE) method. It was found that the average galvanic current of the Cu and Cu–Sn alloy, which shifted from the cathode at 35°C to the anode at 80°C, increased as temperature increased during the immersion time. In contrast, the average galvanic current of Cu–Zn alloy can be ranked as 35°C > 55°C > 80°C. A sudden conversion was that the anode average current of Cu–Zn alloy at 35, 55°C changed into the cathode when the immersion time lasted untill 3 h at 80°C. The results indicate that it is feasible to study the corrosion behaviour under the different temperature environment with the WBE method.